TRAVEL PATTERNS OF TOURISM IN WAKATOBI REGENCY SOUTH EAST SULAWESI PROVINCE - Rizki; Windra Aini; Muh. Rusdi; Mukarramah Machmud; Moh Ridwan (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2025)
This study aims to: 1) identify the tourism potential and components found in Wakatobi Regency, and 2) design a travel pattern that can serve as a reference for regional tourism development. A qualitative research method with a descriptive approach was employed, using data collection techniques such as observation and interviews.The findings indicate that the existence of the 5A+3S components (Accessibility, Accommodation, Attraction, Amenities, Activities, as well as Security, Safety, and Sanitation) has supported tourism development in Wakatobi. However, several challenges remain, including limited accessibility, inadequate supporting facilities, and a shortage of professional instructors in marine tourism activities. The proposed travel pattern is divided into five main clusters: single point, base site, stop over, chaining loop, and complex neighbourhood, with durations ranging from half-day and full-day trips to two-day-one-night and eight-day-four-night itineraries. This travel pattern is designed to accommodate tourist needs and preferences while serving as a guide for the Tourism Office and travel business operators in developing effective and competitive tour packages.